Predonation fears identify young donors at risk for vasovagal reactions. Issue 9 (2nd July 2019) - France, Christopher R.; France, Janis L.; Conatser, Robert; Lux, Pete; McCullough, Jeannine; Erickson, Yasuko
Abstract : BACKGROUND: Extending existing research on the relationship between predonation fear of having blood drawn and risk for vasovagal reactions among young donors, this study assessed the predictive power of specific donation‐related fears. STUDY DESIGN AND METHODS: After the health screening, high school whole blood donors (59.5% female) were randomly assigned into one of three groups. Group 1 (n = 881) answered a control question about their prior night's sleep. Group 2 (n = 911) answered the sleep question and a question about fear of having blood drawn. Group 3 (n = 924) answered the sleep question, the fear of having blood drawn question, and four questions about specific donation‐related fears (seeing blood, needles, pain, and fainting). RESULTS: The proportion of vasovagal reactions did not differ significantly among the groups, indicating that asking one or more fear questions before donation did not promote reactions. Fearful donors were more likely to have a vasovagal reaction, even after controlling for other important demographic and health predictors, with odds ratios ranging from 2.17 (95% confidence interval [CI], 1.44‐3.27) for fear of fainting to 3.50 (95% CI, 2.34‐5.23) for fear of seeing blood. Hours of sleep was not significantly related to vasovagal reaction risk. CONCLUSION: Predonation fear identifies donors who are more likely to experience a vasovagal reaction and does so without increasing the risk of such reactions. Accordingly, fear should be assessed during screening to identify those who could benefit from instruction in anxiety management and who might require greater attention to help prevent donor injury.